HEPATITIS B VACCINATION COVERAGE AND POSTVACCINATION SEROLOGIC TESTING AMONG MEDICAL STUDENTS AT A PUBLIC UNIVERSITY IN BRAZIL - Souza, Eduardo Pernambuco de; Teixeira, Marcelo de Souza (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The aim of this cross-sectional study was to determine the hepatitis B vaccination coverage among medical students at a public university in Rio de Janeiro, Brazil, and their compliance with the postvaccination serologic testing recommendations. Of the total of 858 students, 675 (78.7%) participated in the study. Among the participants, 48.9% (95% CI: 45.1% to 52.7%) were vaccinated against hepatitis B (received ≥ 3 doses of the vaccine), 31.6% were not (received 0, 1 or 2 doses), and 19.6% did not know their vaccination status. Hepatitis B vaccination coverage increased from 26.0% among first-year students to 70.6% among sixth-year students while the prevalence of unknown vaccination status decreased from 39.7% among first-year students to 2.4% among sixth-year students. The frequency of unvaccinated students ranged from 23.7% among fifth-year students to 34.4% among first-year students. Only 34.8% of the vaccinated students performed the anti-HBs testing after vaccination. Among these medical students, we found a low adherence to the hepatitis B vaccination and to the postvaccination serologic testing. A comprehensive hepatitis B immunization program should be offered to students at this medical school.